Impact of Human Resources on Implementing an Evidence-based HIV Prevention Intervention - McKay, Virginia R. (AIDS Behav, 2017)
Evidence-based interventions (EBIs) often require competent staff, or human resources (HR), for implementation. The empirical evidence characterizing the influence of HR fluctuations on EBI delivery is limited and conflicting. Using the Interactive Systems Framework, we explored staff fluctuation and the subsequent influence on RESPECT, an HIV prevention EBI. METHODS: We conducted interviews with staff in two waves (n=53, Wave I; n=37, Wave II) in a national sample of organizations delivering RESPECT (N=29). We analyzed interviews qualitatively to describe changes among RESPECT staff and explore the subsequent influences on RESPECT implementation. RESULTS: Organizations reported downsizing, turnover, and expansion of staff positions. Staff changes had multiple influences on RESPECT implementation including clients reached, fidelity to specific RESPECT protocols, and overall sustainability of RESPECT over time. DISCUSSION: HR fluctuations are common, and our analyses provide an initial characterization of the relationship between HR fluctuation and EBI implementation. Given the prominent influence of HR on EBI implementation, the Interactive Systems Framework is a useful guiding tool for future examinations.